The Effect of Psychological Well-being and Work-life Balance on Employee Performance with Organizational Commitment as a Mediator in the Directorate General of Protocol and Consular - Tams, Nur Fadli; Harsasi, Meirani; Ubud, Sahnaz (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to analyze the influence of psychological well-being and work-life balance on employee performance with organizational commitment as a mediating variable. The background to this research is based on the existence of an evidence gap or inconsistency in findings in previous studies regarding the relationship between psychological well-being and work-life balance on employee performance, as well as the relationship between organizational commitment and employee performance. In addition, this research highlights the importance of managerial commitment as a mediator in the relationship between these variables. The study was conducted on 143 employees within the Directorate General of Protocol and Consular of the Ministry of Foreign Affairs of the Republic of Indonesia. Variable measurements were carried out using a Likert scale, and data analysis was carried out using the Structural Equation Model (SEM) method using the SMART PLS application. The research results show that psychological well-being significantly affects employee performance through organizational commitment with an estimated coefficient of 0.180, a T-statistic of 3.333, and a P-value of 0.001. Furthermore, work-life balance also significantly affects employee performance through organizational commitment with an estimated coefficient of 0.241, T-statistic of 2.805, and P-value of 0.005. These results confirm that organizational commitment mediates the relationship between psychological well-being and work-life balance on employee performance. These findings provide theoretical contributions to understanding the mechanisms of relationships between variables and practical implications for organizations in improving employee performance. Paying attention to employees' psychological well-being and work-life balance and strengthening organizational commitment can increase work effectiveness and productivity.